Effect of orally administered vibrio bacterin on immunity, survival and growth in tiger shrimp (Penaeus monodon) grow‐out culture ponds. (7th November 2017) - Ray, A.K.; Gopal, C.; Solanki, H.G.; Ravisankar, T.; Patil, P.K.
Abstract: Vibriosis is one of the important diseases causing economic loss to the shrimp industry worldwide. The present study reports field observations on the immune stimulatory effect of vibrio bacterin in commercial tiger shrimp ( Penaeus monodon ) grow‐out culture ponds ( n  = 62) which were grouped under three stocking densities; low (6–8 nos per m 2 ), medium (9–11 nos per m 2 ) and high (12–14 nos per m 2 ). The bacterin was administered in feed as a top dressing at final concentration equivalent to 2 × 10 8 CFU per kilogram feed twice a week throughout the culture period. In 20 representative ponds, total haemocyte count and prophenoloxidase activity in shrimp were significantly ( P  < 0·05) higher and anatomical deformities like, antennae cut (5·02 ± 2·42), tail rot (5·10 ± 1·74), rostrum cut (4·49 ± 2·19) and soft shell (10·05 ± 5·77) were significantly lower compared to controls in all the studied stocking densities. Significant ( P  < 0·05) improvement in production parameters like survival and production (kg ha 1 ) was observed in all treatment ponds while similar improvement in average daily gain and feed conversion ratio could be observed in groups with low and medium stocking densities. Results of the study suggest that, oral administration of vibrio bacterin improves the immunity, reduces anatomical deformities and enhances the production in commercial shrimp culture operations. Significance and Impact of the Study: Administration of vibrio bacterin in feed as a top dressing induced immune stimulation as indicated by higher levels of total haemocyte count and prophenoloxidase. Further reduction in percentage of animals with anatomical deformities suggests the protection against subclinical bacterial infections. The overall improvement in the production parameters like, average daily gain, survival, feed conversation ratio and production in different shrimp stocking densities under commercial farming conditions suggested the possible development of an immune stimulant product based on the inactivated vibrio bacteria for improved health and production in Penaeus monodon shrimp farming. Abstract : Significance and Impact of the Study: Administration of vibrio bacterin in feed as a top dressing induced immune stimulation as indicated by higher levels of total haemocyte count and prophenoloxidase. Further reduction in percentage of animals with anatomical deformities suggests the protection against subclinical bacterial infections. The overall improvement in the production parameters like, average daily gain, survival, feed conversation ratio and production in different shrimp stocking densities under commercial farming conditions suggested the possible development of an immune stimulant product based on the inactivated vibrio bacteria for improved health and production in Penaeus monodon shrimp farming.